Twenty Years: Reflections and Questions - Alice Brand (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Recalling her lifelong research into the connection between emotions and writing, the first editor of JAEPL critiques scholarly contexts that limit the exploration of knowledge about writing.